2020
DOI: 10.3389/fimmu.2020.00803
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary (i.pulmon.) Pull Immunization With the Tuberculosis Subunit Vaccine Candidate H56/CAF01 After Intramuscular (i.m.) Priming Elicits a Distinct Innate Myeloid Response and Activation of Antigen-Presenting Cells Than i.m. or i.pulmon. Prime Immunization Alone

Abstract: Understanding the in vivo fate of vaccine antigens and adjuvants and their safety is crucial for the rational design of mucosal subunit vaccines. Prime and pull vaccination using the T helper 17-inducing adjuvant CAF01 administered parenterally and mucosally, respectively, has previously been suggested as a promising strategy to redirect immunity to mucosal tissues. Recently, we reported a promising tuberculosis (TB) vaccination strategy comprising of parenteral priming followed by intrapulmonary (i.pulmon.) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…It is a combination of Ag85B, ESAT-6, and Rv660c. In a recent preclinical trial, the vaccine H56: CAF01 has shown activation of both innate and adaptive immunity in mice [ 48 ]. This study and others showed hope for new subunit delivery strategies [ 49 ].…”
Section: Subunit/adjuvanted Vaccinesmentioning
confidence: 99%
“…It is a combination of Ag85B, ESAT-6, and Rv660c. In a recent preclinical trial, the vaccine H56: CAF01 has shown activation of both innate and adaptive immunity in mice [ 48 ]. This study and others showed hope for new subunit delivery strategies [ 49 ].…”
Section: Subunit/adjuvanted Vaccinesmentioning
confidence: 99%
“…2). The sustained presence of adjuvant following delivery has also been previously characterised for spray-dried H56/CAF01, which is present within the lungs 14 days following pulmonary vaccination, 30 and Alum-adjuvanted vaccines which have detectable aluminium in tissue up to 9 months following subcutaneous or intramuscular delivery. 31 Given the delicate nature of the respiratory mucosa, the persistence of adjuvant may be concerning in its potential to induce prolonged local inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…17 While the dynamics of leucocyte responses to parenteral adjuvant administration have been characterised, there are few detailed analyses of innate immune cell recruitment, uptake and activation induced by pulmonary adjuvant candidates and greater understanding in this area is still required. [18][19][20] In the present study, fluorescein-conjugated Advax was administered intratracheally (i.t.) either alone or with the CysVac2 fusion protein, a TB vaccine candidate that is highly immunogenic and protective in pre-clinical studies and generates enhanced protection when administered as a pulmonary vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally-derived carbohydrate particles such as delta inulin (Advax), chitosan, and Bacillus subtilis spores have all been utilised as mucosal adjuvants in TB vaccine candidates, all producing a Th 1 /Th 17 phenotype alongside increased pulmonary IgA (37,(114)(115)(116). CAF01 has been tested intranasally and has also been spray-dried for intrapulmonary administration (107). Th 17 immunity is often achieved via mode of administration, as it has been observed across multiple vaccine platforms that mucosal vaccination, particularly intranasal, favours Th 17 differentiation (117,118).…”
Section: Cell Targeting Via Mucosal Administrationmentioning
confidence: 99%
“…These important innate immune effector cells can be uniquely targeted via intranasal and/or intrapulmonary vaccination. Several groups have explored a “prime-pull” strategy which takes advantage of both parenteral vaccine (prime) and mucosal vaccine boost (pull) to direct antigen-specific T RM to the lungs ( 107 , 108 ).…”
Section: Targeting Specific Immune Cellsmentioning
confidence: 99%